Polyethylene glycol as a de-aggregating agent in the preparation of celecoxib loaded gelatin microspheres - THAKKAR, H; MURTHY, RSR (Ars Pharmaceutica (Internet))
Gelatin microspheres with high entrapment efficiency were prepared using emulsification chemical crosslinkingmethod using polyethylene glycol as a de-aggregating agent. Two different cross-linking agentsviz. formaldehyde and glutaraldehyde were used for cross-linking gelatin. The prepared microsphereswere characterized for entrapment efficiency, particles size, in-vitro drug release and the morphologywas studied by scanning electron microscopy. The FTIR studies indicated that there is no chemicalinteraction between gelatin and PEG. PEG acts only as a barrier to the aggregation of the gelatinmicrodrops present in the internal phase of the emulsion, while preparation. In-vitro drug release studiesindicated that the microspheres cross-linked using glutaraldehyde showed slower release rate than thosecross-linked with formaldehyde. Burst release was observed in both the cases. In general, about 40%of the drug is released in the first hour followed by a slow release for about 96 hours for glutaraldehydecross-linked microspheres.